Learner support in a distributed learning environment:the use of WWW-based teachware packages - Christian Langenbach; Freimut Bodendorf (Information Research: An International Electronic Journal)
Various forms of education and training, based on the classical Computer Based Training (CBT), have become well established within companies and in higher education. With regard to the flexibility in terms of time and location, as well as in terms of incurred cost, they are far superior to traditional forms of instruction. A relatively recent development which has not yet gained widespread acceptance is the use of the World Wide Web (WWW) as a basis and platform for distributed computer assisted teaching and learning. In addition to the advantages outlined with regard to classical CBT, the WWW offers the two advantages of world wide availablity as well as ease of promptly updating courses, but also adds many possibilities of collaborative learning. Using the Java programming language and the ever improving means of online presentation it has become possible to realize sophisticated WWW-based teachware packages which are comparable in terms of appearance and functionality to classical CBT applications created with dedicated authoring systems.